Assessment of cervical lymph node metastasis for therapeutic decision-making in squamous cell carcinoma of buccal mucosa: a prospective clinical analysis - Essig, Harald (BioMed Central, 2012)
BACKGROUND: Cervical metastasis has a tremendous impact on the prognosis in patients with carcinomas of the head and neck and the frequency of such spread is greater than 20% for most squamous cell carcinomas. With emerging evidence, focus is shifting to conservative neck procedures aimed at achieving good shoulder function without compromising oncologic safety. The purpose of this study was to analyze the pattern of nodal metastasis in patients presenting with squamous cell carcinoma of buccal mucosa. MATERIALS AND METHODS: This was a prospective clinical analysis of patients who were histologically diagnosed with squamous cell carcinoma of the buccal cavity and clinically N1 and had not received treatment anywhere else. Patients were analyzed for age and sex distribution, tumor staging, location, and metastasis. RESULTS: The incidence of metastatic lymph node in T4 (n=44) was the highest, that is, level I was 100% (44/44), level II was 43.18% (19/44), level III was 15.90% (7/44), and level IV was 4.5% (2/44). Level V was free of metastasis. Among T3 (n=10) lesions, incidence of metastasis in level I was 100% (10/10), level II was 20% (2/10), and level III, IV, and V were free of metastasis. Among T2 (n=6) lesions, incidence of lymph node metastasis in level I was 100% (6/6) and all other levels of lymph nodes were found free of metastasis. CONCLUSION: Lymphatic spread from carcinoma of the buccal mucosa is low. Involvement of level IV is seen in only 3% of patients. A more conservative approach to the neck in patients with carcinoma of the buccal mucosa is recommended.